Synergistic Effect of Sodium Chlorite and Edible Coating on Quality Maintenance of Minimally Processed Citrus grandis under Passive and Active MAP. Issue 8 (3rd July 2015) - Ban, Zhaojun; Feng, Jianhua; Wei, Wenwen; Yang, Xiangzheng; Li, Jilan; Guan, Junfeng; Li, Jiang
Abstract Edible coating has been an innovation within the bioactive packaging concept. The comparative analysis upon the effect of edible coating, sodium chlorite (SC) and their combined application on quality maintenance of minimally processed pomelo (Citrus grandis) fruits during storage at 4 °C was conducted. Results showed that the combination of edible coating and SC dipping delayed the microbial development whereas the sole coating or dipping treatment was less efficient. The synergetic application of edible coating and SC treatment under modified atmosphere packaging (MAP, 10% O2, 10% CO2) was able to maintain the total soluble solids level and ascorbic acid content, while reduce the weight loss as well as development of mesophiles and psychrotrophs. Nonetheless, the N, O‐carboxymethyl chitosan solely coated samples showed significantly higher level of weight loss during storage with comparison to the untreated sample. Furthermore, the combined application of edible coating and SC dipping under active MAP best maintained the sensory quality of minimally processed pomelo fruit during storage.